Blood flow restriction exercise in high-performance sport settings: A practitioner survey - Clarkson, M. J.; Scott, B. R.; Patterson, S. D.; Warmington, S. A. (Journal of Sports Sciences, 2025)
The purpose of this study was to characterise how blood flow restriction (BFR) exercise is utilised by practitioners in high-performance sports settings. Participants (n = 154) engaged with the questionnaire, of which 123 provided data about their use of BFR with athletes in high-performance sports settings. The main findings indicated that BFR was primarily used for injury rehabilitation (81.3% of practitioners) or supplementary to traditional strength and conditioning programs for muscle hypertrophy (80.4%), limiting loss of muscle mass (71.9%), or muscle strengthening (51.6%). Participants used BFR with both team and individual sports, but with only a small subset of the athletes they worked with (65% of practitioners used BFR with less than 25% of their athletes). Cuff pressures were prescribed using both measured individualised occlusion pressures (56.1%) and arbitrary set pressures (52.8%). Despite practitioners` awareness of contraindications and the need for screening, formal screening tools were underutilised (55.7% of practitioners did not use a screening tool for clearance to use BFR). Ultimately, BFR exercise was largely prescribed in line with established guidelines, although the application of individualised cuff pressures and health screening processes may require further attention from practitioners in high-performance sports.